Factors for converting to organic farming in Malaysia / Anisah Mohammed … [et al.] - Mohammed, Anisah; Yusop, Mohamad Amir Shah; Abdul Aziz, Noorshilawati; Abdullah, Nur Suraya; Rosli, Fazidah; Muhamad Ridzwan, Hendrie Johann (2013)
Organic farming is a philosophy and a system of farming in value that reflects an awareness of ecology, social realities and the ability of individual to take effective actions in agricultural activities. In Malaysia, organic farming is still very young and slow growing industry. Department of Agriculture Malaysia was responsible for observing the development of organic farming and also published a standard for certified organic production under Malaysian Organic Scheme (SOM). The study was conducted to identify the factors for converting to organic farming in Malaysia among the certified organic farmers and organic farmers waiting for SOM certification. Questionnaire and interview were carried out to collect the data. No chemical residues, reduced high risk of diseases, providing of good health, good in taste and nutrients of organic produces, reduced environmental pollution, preservation of biological diversities, efficient uses of natural resources, increasing consumers demand, providing safety produce to consumers, and high market potential were the major factors for converting to organic farming in Malaysia.